New Distribution Records of Some Orchids from Chhattisgarh State (Kanger Valley National Park), India - Kotia, Amit; Kumar, Pankaj; Tiwari, Umesh Kumar L.; Parsad, Amar Nath; Rawat, Gopal Singh (Indian Forester, 2010)
Dendrobium peguanum Lindl. and Liparis deflexa J.D.Hook, are two orchid species which are reported for the first time from Chhattisgarh state (Kanger Valley National Park) or we can say past Madhya Pradesh state. The present article deals with the description and distribution map of the species.